A Medicinal Herb Scutellaria lateriflora Inhibits PrP Replication in vitro and Delays the Onset of Prion Disease in Mice - Eiden, Martin; Leidel, Fabienne; Strohmeier, Barbara; Fast, Christine; Groschup, Martin H. (Frontiers in Psychiatry, 2012)
ABSTRACT Transmissible spongiform encephalopathies (TSE) are characterized by the misfolding of the host encoded prion protein (PrPC) into a pathogenic isoform (PrPSc) which leads to the accumulation of -sheet-rich fibrils and subsequent loss of neurons and synaptic functions. Although many compounds have been identified which inhibit accumulation or dissolve fibrils and aggregates in vitro there is no therapeutic treatment to stop these progressive neurodegenerative diseases. Here we describe the effects of the traditional medicinal herb Scutellaria lateriflora (S. lateriflora) and its natural compounds, the flavonoids Baicalein and Baicalin, on the development of prion disease using in vitro and in vivo models. S. lateriflora extract as well as both constituents reduced the PrPres accumulation in scrapie-infected cell cultures and cell-free conversion assays and lead to the destabilization of preexisting PrPSc fibrils. Moreover, tea prepared from S. lateriflora, prolonged significantly the incubation time of scrapie infected mice upon oral treatment. Therefore Scutellaria extracts as well as the individual compounds can be considered as promising candidates for the development of new therapeutic drugs against TSEs and other neurodegenerative diseases like Alzheimer’s and Parkinson’s disease.